Strategi Pengembangan Sumber Daya Manusia, Pariwisata, dan Digitalisasi sebagai Pilar Keberlanjutan Ekonomi Lokal di Desa Sukamulya, Sematang Borang - Fanny, Gita Trisna (Universitas Nusantara PGRI Kediri, 2025)
The Community Service Program (KKN) implemented in Sukamulya Village, Sematang Borang District, aims to formulate a strategy for sustainable local economic development through three main pillars: human resource development (HRD), tourism sector, and digitalization. The problems faced by this village include limited access to skills training, tourism potential that has not been optimally developed, and low utilization of information technology in community economic activities. The methods used in this activity include direct observation, interviews with the community and village officials, and the implementation of training and socialization based on local needs. The results of the activity show that increasing HR capacity through entrepreneurship training, digital literacy, and management of MSME products has a positive impact on community motivation and independence. In the tourism sector, mapping local potential such as agrotourism and village culture is the basis for developing destinations based on community participation. Meanwhile, digitalization is applied through the creation of village promotional media and training in the use of digital platforms for marketing local products. The integration of these three pillars forms an inclusive and sustainable local economic development ecosystem. Thus, this strategy not only strengthens the competitiveness of Sukamulya Village economically, but also opens up space for active community participation in development. The recommendation of this program is the need for ongoing support from local governments and partnerships with external parties so that digital transformation and the village economy can run consistently and sustainably.